Reasons for fake news dissemination: a systematic review - Saharrudin, Nurul Farhana; Ahmad Ghazali, Akmar Hayati; Ismail, Ismi Arif; Arshad, Mohd Mursyid; Mohd Zawawi, Julia Wirza; Wan Mokhtar, Wan Ikhlas (Human Resource Management Academic Research Society, 2023)
Fake news has lately gained popularity, yet little study has been done on the topic. Social media platforms facilitate the quick dissemination of this false information and make determining the reliability of internet sources more challenging. Therefore, the purpose of this study is to perform a thorough literature analysis on the factors that contribute to the spread of false information. Five key methodological steps were used in the review processes: formulation of research questions, guided by the review protocol; systematic search strategies based on identification, screening, and eligibility on several reputable databases, including Scopus, Science Direct, Google Scholar, and Dimension; quality assessment; and data extraction and analysis. Four main themes were developed in this review, namely (1) information seeking and sharing, (2) poor media literacy; (3) trustworthiness; and (4) misuse of AI technology. These four themes are divided into 10 sub-themes.